2016
DOI: 10.1002/app.43956
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency of silver‐based antibacterial additives and its influence in thermoplastic elastomers

Abstract: Styrene-butylene/ethylene-styrene-based thermoplastic elastomers (TPE) are polymers with soft touch properties that are widely used for manufacturing devices that involve hand contact. However, when contaminated with microorganisms these products can contribute to spreading diseases. The incorporation of antibacterial additives can help maintain low bacteria counts. This work evaluated the antibacterial action of TPE loaded with silver ions and silver nanoparticles. The additives nanosilver on fumed silica (Np… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 57 publications
0
8
0
1
Order By: Relevance
“…It can be explained by the difference in the cell wall structure. The thick peptidoglycan cell wall of Gram-positive bacteria protects its cell from silver penetration while Gramm-negative bacteria lack this protection [ 60 , 61 ]. Similar effect of the cell wall may apply for the case of Zn 2+ ions as well as for ROS action [ 56 , 57 , 62 ].…”
Section: Resultsmentioning
confidence: 99%
“…It can be explained by the difference in the cell wall structure. The thick peptidoglycan cell wall of Gram-positive bacteria protects its cell from silver penetration while Gramm-negative bacteria lack this protection [ 60 , 61 ]. Similar effect of the cell wall may apply for the case of Zn 2+ ions as well as for ROS action [ 56 , 57 , 62 ].…”
Section: Resultsmentioning
confidence: 99%
“…In styrene-ethylene/butylene-styrene (SEBS)-based TPE matrices, the metal particles have the tendency to remain in the SEBS/oil phase (Tomacheski et al, 2016). The amorphous part of the polymer matrix is prone to oxidation; whereas the crystalline phase of the polymer is more susceptible to a molecular reorganization, such as chains fragmentation (Corti et al, 2010).…”
Section: Resultsmentioning
confidence: 99%
“…Generally, Gram-negative bacteria are more resistant to antibacterial agents than Gram-positive bacteria due to the complexity of the cell membrane of Gram-negative, which hinders the entry and, consequently, the diffusion of the AgNPs into these microorganisms 26 . Based on studies with individual strains from different cultures, Tomacheski et al 27 reported that S. aureus is more resistant to AgNPs in comparison to to E. coli. In this way, the authors showed that the bactericidal efficiency of the nanoparticles does not depend only on the structure of the bacterial membrane.…”
Section: Antibacterial Activitymentioning
confidence: 99%
“…However, some mechanisms of toxicity are suggested: a) the contribution of free silver ions followed by disruption of ATP production and DNA replication (AgNPs act on the phosphate of DNA molecules resulting in the inactivation of their replication); b) formation of oxygen reactive species by the ions and AgNPs. These molecules react with the sulfhydryl -SH groups of the cell wall to form R-S-S-R blocking respiration, and causing cell death; c) direct damage of the cell membrane by AgNPs, affecting the permeability of the membrane 27 .…”
Section: Antibacterial Activitymentioning
confidence: 99%